The Victorian Reformation Bible: Acts and Monuments. Issue 1 (1st April 2014) - Westbrook, Vivienne
Abstract: In 1611 the King James Bible was printed with minimal annotations, as requested by King James. It was another of his attempts at political and religious reconciliation. Smaller, more affordable, versions quickly followed that competed with the highly popular and copiously annotated Bibles based on the 1560 Geneva version by the Marian exiles. By the nineteenth century the King James Bible had become very popular and innumerable editions were published, often with emendations, long prefaces, illustrations and, most importantly, copious annotations. Annotated King James Bibles appeared to offer the best of both the Reformation Geneva and King James Bible in a Victorian context, but they also reignited old controversies about the use and abuse of paratext. Amid the numerous competing versions stood a group of Victorian scholars, theologians and translators, who understood the need to reclaim the King James Bible through its Reformation heritage; they monumentalized it.